The Vascular-Dependent and -Independent Actions of Calcitonin Gene-Related Peptide in Cardiovascular Disease - Argunhan, Fulye; Brain, Susan D. (Frontiers in Physiology, 2022)
The treatment of hypertension and heart failure remains a major challenge to healthcare providers. Despite therapeutic advances, heart failure affects more than 26 million people worldwide and is increasing in prevalence due to an ageing population. Similarly, despite an improvement in blood pressure management, largely due to pharmacological interventions, hypertension remains a silent killer. This is in part due to its ability to contribute to heart failure. Development of novel therapies will likely be at the forefront of future cardiovascular studies to address these unmet needs. Calcitonin gene-related peptide (CGRP) is a 37 amino acid potent vasodilator with positive-ionotropic and -chronotropic effects. It has been reported to have beneficial effects in hypertensive and heart failure patients. Interestingly, changes in plasma CGRP concentration in patients after myocardial infarction, heart failure, and in some forms of hypertension, also support a role for CGRP on hemodynamic functions. Rodent studies have played an important role thus far in delineating mechanisms involved in CGRP-induced cardioprotection. However, due to the short plasma half-life of CGRP, these well documented beneficial effects have often proven to be acute and transient. Recent development of longer lasting CGRP agonists may therefore offer a practical solution to investigating CGRP further in cardiovascular disease in vivo. Furthermore, pre-clinical murine studies have hinted at the prospect of cardioprotective mechanisms of CGRP which is independent of its hypotensive effect. Here, we discuss past and present evidence of vascular-dependent and -independent processes by which CGRP could protect the vasculature and myocardium against cardiovascular dysfunction.